Readiness of patients with malignant brain tumours for video-based online visits and medical assessments: German Medical Science GMS Publishing House - Weiß-Lucas, Carolin; Dechange, Luisa; Jost, Johanna; Jonas, Kristina; Wiewrodt, Dorothee; Goldbrunner, Roland (73. Jahrestagung der Deutschen Gesellschaft für Neurochirurgie (DGNC), Joint Meeting mit der Griechischen Gesellschaft für Neurochirurgie)
Objective: Regular follow-up visits are essential to ensure adequate monitoring of brain tumour patients. However, access to such visits can be limited, e.g., due to weak infrastructure or patient co-morbidity. Video-based online visits (OV) have attracted attention as an alternative to in-person visits, [for full text, please go to the a.m. URL]
Keywords: Medicine and health

Combining multiple tasks to identify clinically essential language tracts using fMRI-informed tractography: German Medical Science GMS Publishing House - Lieker, Emma; Nettekoven, Charlotte; Keil, Phillip; Louçäo, Ricardo; Jonas, Kristina; Lichtenstein, Thorsten; Picht, Thomas; Goldbrunner, Roland; Weiß-Lucas, Carolin (73. Jahrestagung der Deutschen Gesellschaft für Neurochirurgie (DGNC), Joint Meeting mit der Griechischen Gesellschaft für Neurochirurgie)
Keywords: Medicine and health

Quantitative analysis of speech onset and object naming in rTMS-guided language mapping: German Medical Science GMS Publishing House - Louçäo, Ricardo; Zalgaj, Samim; Pieczewski, Julia; Neuschmelting, Volker; Grefkes, Christian; Goldbrunner, Roland; Jonas, Kristina; Nettekoven, Charlotte; Weiß-Lucas, Carolin (73. Jahrestagung der Deutschen Gesellschaft für Neurochirurgie (DGNC), Joint Meeting mit der Griechischen Gesellschaft für Neurochirurgie)
Keywords: Medicine and health

Determining language function lateralisation using clustered-sparse acquisition fMRI: German Medical Science GMS Publishing House - Keil, Phillip; Nettekoven, Charlotte; Jonas, Kristina; Lichtenstein, Thorsten; Goldbrunner, Roland; Weiß-Lucas, Carolin (73. Jahrestagung der Deutschen Gesellschaft für Neurochirurgie (DGNC), Joint Meeting mit der Griechischen Gesellschaft für Neurochirurgie)
Keywords: Medicine and health

Digitale Sprachdiagnostik im Schulalter - Jonas, Kristina; Jaecks, Petra (Sprachförderung und Sprachtherapie in Schule und Praxis)

Fazialisparesen: Herausforderungen für Diagnostik und Therapie in der Sprachtherapie - Gerhards, L.; Hembach, P.; Jonas, Kristina (Forum Logopädie)

Kognitive Kommunikationsstörungen: Wenn die Zusammenarbeit von Sprache und geistigen Fähigkeiten durch eine neurologische Erkrankung beeinträchtigt ist - Büttner-Kunert, Julia; Jonas, Kristina; Rosenkranz, Anna; Thöne-Otto, Angelika

Neues interdisziplinäres DFG-Netzwerk gestartet - Kognitive Kommunikationsstörungen bei Schädel-Hirn-Trauma: Die Interaktion von Sprache, Kognition und Verhalten aus interdisziplinärer Perspektive - Büttner-Kunert, J.; Jonas, K. (logos)

Entwicklungsverläufe kindlicher Dysarthrien: Auditive Profile und Verständlichkeit - Haas, E.; Ziegler, W.; Scholderle, T. (Neurologie {&} Rehabilitation)

Forschungsprojekt KoliPENs: Kognitive, linguistische und personenbezogene Einflussfaktoren auf das Schreiben - Albrecht, K.; Jaecks, Petra; Jonas, K.; Stegenwallner-Schütz, M.; Lehmden, F. (Sprachtherapie aktuell: Praxis – Beruf – Verband)